2006
DOI: 10.1590/s0034-70942006000400005
|View full text |Cite
|
Sign up to set email alerts
|

Analgesia pós-operatória para cesariana: a adição de clonidina à morfina subaracnóidea melhora a qualidade da analgesia?

Abstract: The addition of clonidine to spinal anesthesia with 0.5% hyperbaric bupivacaine (12.5 mg) and morphine (100 microg) for cesarean section improved the quality of the postoperative analgesia without increasing the incidence of side effects. We suggest that the dose of 15 microg of clonidine should be used.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
10
0
5

Year Published

2012
2012
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 4 publications
1
10
0
5
Order By: Relevance
“…also concluded that addition of IT clonidine did not adversely affect the neonatal outcome in terms of APGAR scores. [21920]…”
Section: Discussionmentioning
confidence: 99%
“…also concluded that addition of IT clonidine did not adversely affect the neonatal outcome in terms of APGAR scores. [21920]…”
Section: Discussionmentioning
confidence: 99%
“…Combination of clonidine and opioids (morphine, fentanyl, sufentanil) with local anesthetics has been a very common practice because it improves the quality of intraoperative analgesia and prolongs postoperative analgesia in addition to allowing the use of smaller doses of local anesthetics, with reduced risk of maternal hypotension and harm to the fetus [1][2][3][4][5]7,8,18 . Morphine contributes little to the quality of surgical analgesia due to its pharmacodynamic characteristics, such as slow onset of action and prolonged duration.…”
Section: Discussionmentioning
confidence: 99%
“…This action enhances the effects of local anesthetics, indirectly reduces its absorption by the postsynaptic vasoconstrictive effect of α 2 -receptors, and improves the quality of anesthetic block, both regarding the duration of surgical anesthesia and motor block 4,5 . When used in neuraxis, the analgesic effect of clonidine is evident due to the action on spinal and supraspinal α 2 -adrenergic receptors in central nervous system (CNS), which includes the activation of α 2 -postsynaptic receptors of noradrenergic descending pathways of cholinergic neurons and nitric oxide release and enkephalin-like substances 5,7 . In addition to the analgesic properties, it has also antihyperalgesic properties, which reinforces the noradrenergic inhibitory effect on dorsal horn of spinal cord 8 .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations